Nomenclatural changes in Bulbophyllum (Orchidaceae; Epidendroideae) - Vermeulen, Jaap J.; Schuiteman, André; de Vogel, Eduard F. (Phytotaxa, 2014)
New combinations in Bulbophyllum (Orchidaceae) are made to correspond to the revised classification of the genus in Genera orchidacearum, vol. 6. Several new sections introduced in that publication are formally described and validated here.